Hygienic practices and factors of complementary food preparation among mothers of children aged 6–24 months in Ethiopia: a systematic review and meta-analysis - Zeleke, Agerie Mengistie; Tassew, Worku Chekol; Ayale Ferede, Yeshiwas; Andargie, Tadele Maru (Frontiers in Food Science and Technology, 2024)
Background: A child’s transition to complementary food (CF) feeding is important, and it should be ensured that CF is prepared, stored, and fed in a hygienic manner using clean hands, dishes, and utensils to prevent infections. However, there are no comprehensive review statistics available at the national level. Hence, the aim of this study is to determine the hygienic practices of complementary food preparation and its factors among Ethiopian women with children between the ages of 6 and 24 months. Methods: On the nationwide prevalence of hygienic practices during the preparation of complementary foods and their determinants among mothers of children aged 6–24 months in Ethiopia, a systematic review and meta-analysis were performed. We searched in PubMed, ScienceDirect, Scopus, African Journal Online (AJOL), Google Scholar, and the websites to identify studies that were published until March 2023. We performed this review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A random-effects meta-analysis was done using StatsDirect statistical software and Open Meta Analyst to estimate the prevalence of hygienic practices, and the results were reported in a forest plot. Simple charts and tables were used to summarize the evidence on complementary food preparation and determinates. Results: Nine studies involving 4,403 mothers were included in this Ethiopian study. The overall prevalence of good hygienic practices during complementary food preparation among mothers who have children aged 6–24 months was 46.53% (95% CI: 28.13–64.94) (p < 0.0001). Having a separate kitchen (AOR = 6.78; 95% CI: 1.04–44.20), having a three-bowl washing facility in their houses (AOR = 10.61; 95% CI: 7.31–15.41), mothers’ access to media (AOR = 4.81; 95% CI: 1.23–18.82), and urban residence (AOR = 4.78; 95% CI: 2.73–8.38) were the predictors of good hygienic practice during complementary food preparation. Conclusion: Regarding the prevalence of hygienic procedures among the mothers of children aged 6–24 months nationwide when preparing complementary foods, there is a significant lack of hygienic behavior among Ethiopian mothers. Hence, the Ethiopian ministries of health focus on designing complementary food guidelines for the prenatal healthcare system. Furthermore, health extension workers are also better advised to maintain food hygiene during prenatal care visits, which is recommended to improve good hygienic practices during complementary food preparation in Ethiopia.